2021
DOI: 10.31243/ei.uta.v6i4.1201.2021
|View full text |Cite
|
Sign up to set email alerts
|

Flebitis en Neonatos en Un Hospital De La Provincia De El Oro. Machala-Ecuador

Abstract: Introducción: La flebitis es la inflamación del sistema venoso, con frecuencia ocurre por el uso de catéteres vasculares. Objetivo: Establecer la relación entre la flebitis por catéter venoso periférico y la hospitalización prolongada en los recién nacidos ingresados en el Servicio de Neonatología del Hospital General Teófilo Dávila. Métodos: Estudio observacional, descriptivo, transversal y prospectivo, realizado en el Hospital General Teófilo, Cantón Machala, Ecuador señalado, durante el 2018–2019. La muestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
1
Order By: Relevance
“…The articles whose methodology was used were: Descriptive with 44.4%, prospective 33.4%, exploratory 11.1% and quantitative in 11.1%. Phlebitis is an adverse event present in different hospital areas, and is under the care of the nursing professional, in the systematic review the factors associated with phlebitis were identified in 9 original articles, being classified into intrinsic and extrinsic, intravenous infusions are provided by different circumstances and times of permanence, making it a high risk of presenting safety accidents in the patient (Reyes- Rueda, et al, 2021); (Fortes, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles whose methodology was used were: Descriptive with 44.4%, prospective 33.4%, exploratory 11.1% and quantitative in 11.1%. Phlebitis is an adverse event present in different hospital areas, and is under the care of the nursing professional, in the systematic review the factors associated with phlebitis were identified in 9 original articles, being classified into intrinsic and extrinsic, intravenous infusions are provided by different circumstances and times of permanence, making it a high risk of presenting safety accidents in the patient (Reyes- Rueda, et al, 2021); (Fortes, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to Reyes- Rueda et al, (2021), in his research on the permanence of hospitalized neonates and its relationship with the presence of phlebitis, he concludes that there is an important relationship taking into account some risk factors such as the place of insertion, the number of times it is attempted to cannulate, the length of time spent in hospital and the use of irritant solutions. On the other hand, Gómez-Neva et al, (2015) in their systematic review determined that more research is needed in the population of children regarding the permanence of peripheral catheters and the appearance of phlebitis, the studies were directed to investigate other aspects; unlike adults there is a risk of presenting phlebitis 72 and 96 hours after insertion of the catheter; so it is necessary to perform it in this period and prevent phlebitis (Webster et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…En un estudio realizado en la ciudad de Machala se demuestra que el 95% de neonatos tienen problemas con la infiltración del catéter periférico y un 56.32% de estos sufrió de flebitis condiciones que generan un alto nivel de estrés y dolor en el neonato. (Rueda, de Vizcaino, Maldonado, Arévalo-Córdova, & Zúñiga, 2021) Por esta razón es necesario describir las experiencias que afronta el profesional de enfermería en su diario convivir con el paciente neonatológico que se encuentra hospitalizado en una unidad de cuidados críticos, el objetivo principal de realizar esta investigación es determinar las experiencias del personal de enfermería en el manejo del catéter central de inserción periférica neonatal. En esencia lo que se pretende describir es el sentir de la o el enfermero a cargo de realizar este procedimiento cuáles son sus sensaciones sus miedos y dificultades en su labor son puntos clave para entender tan importante labor.…”
Section: Introductionunclassified